EFFECTIVENESS OF SELF-INSTRUCTIONAL MODULE ON HOME MANAGEMENT OF DIARRHOEA - Suman Lal; Mrs Kavita Sharma; Mr. Ankit Diamond; Ms. Ankita Lal; Mrs. Jincy M Varghese (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Diarrhea disease constitutes a leading cause of morbidity and mortality among children in developing countries. More than 3 million deaths are estimated to result each year the world. Over as a consequence of diarrhea disease in children of under 5 year of age group, 80% of these deaths occur in the first 2 years of age. Objective: 1. To assess the existing knowledge on home management of diarrhea among ANM 1st year students. 2. To evaluate the effectiveness of self- instructional module on home management of diarrhea among ANM 1st year students. 3. To determine the association between the knowledge with their selected demographic variables. Research methodology: Research design: Pre-experimental and evaluative research approach with one group pre-test post-test design with no control group. Setting of study- The present study was conducted in Rohilkhand School of Nursing, Bareilly U.P. Target population- ANM 1st year nursing students selected for study. Sample size-50 ANM 1st year nursing students who fulfilled inclusion and exclusion criteria. Sampling technique-In this study, purposive sampling technique was used. Predesigned and validated tools were used. A structured questionnaire on home management of diarrhea was used for assessment of knowledge. RESULT: On statistical analysis it was found that the knowledge level of nursing students was increased with introduction of SIM on “home management of diarrhea”. The mean pretest knowledge score 19.28 SD 3.301 and posttest knowledge score 27.12 SD 1.686. The paired t test value is 16.12 which was significant at 0.5% level of significance. It shows that there is significant increase in the knowledge after the self-instructional module on home management of diarrhea. The chi-square test shows that there is significant association between knowledge and demographic variables. CONCLUSION: Findings of the provide score evidence that Self-instructional module is an effective teaching strategy in increasing the knowledge regarding home management of diarrhea.